Inter-human perspectivism and ancestor veneration in Late Neolithic/ Bronze Age Southwestern Norway - Sørgaard, Kristine Orestad (Danish Journal of Archaeology, 2025)
The transition of nomadic hunter-gatherers into sedentary farmers marks the beginning of the Neolithic period. However, the Neolithic was more than just a social and economic transition. It signified the onset of a new worldview which re-defined ways of thinking about the world, and the role and place of humans within it. As such, this era encompassed a lot more than simply the adoption of new technologies and the formation of new social structures. Drawing on ethnographic work on north Asian ontologies, this paper argues that the Late Neolithic (LN) transition in Rogaland, Southwestern Norway, was marked by a shift to inter-human perspectivism. This shift was accompanied by a growing interest in ancestral perspectives, leading to an increase in ancestor-oriented rituals that ranged from simple commemorative practices honouring the deceased to elaborate public spectacles and hero cults. While the primary focus of this paper is on the Late Neolithic/ Early Bronze Age, comparative insights from the Late Bronze Age are included, particularly in the discussion of hoards, due to the relative scarcity of material from Rogaland.